The Representation of The Cultural and Social Variations in The Work “Unfinished Memoirs” Of Sheikh Mujibur Rahman Translated from English into Russian Languages - Abushaev Amir Kamilevich (Genius Publishing Group, 2021)
Bangabandhu Sheikh Mujibur Rahman was born in a renowned family in “Tungipara” of Gopalganj on 17 March 1920. He was the third child of Sheikh Lutfur Rahman and Sayera Khatun whose ancestry is traced back to Baghdad, Iraq. From the family history, it is estimated that around 400 years ago, Sheikh Awwal came from Iraq to preach Islam in the eastern part of the Indian subcontinent. Part of the family may have settled in Sonargaon near Dhaka, and another part settled in Gopalganj. Mujib was part of the seventh generation in the Sheikh family, the eldest son of Sheikh Lutfur Rahman and “Sayera” Khatun. His parents were paternal cousin. His maternal grandfather Sheikh Abdul Majid was the elder brother of his paternal grandfather, Sheikh Abdul Hamid. His grandfathers also had a young brother, Sheikh Abdul Rashid who was popularly known as ‘Khan Saheb’ by both the locals and the ruling British Empire
Keywords: Sonargaon; family; subcontinent; flourished